THE DEGREE OF SOIL DEGRADATION AND AEROSOL FORMATION FROM EXPLOSION PRODUCTS RESULTING FROM HOSTILITIES IN UKRAINE - BILYI, Taras; HLAVATSKYI, Dmytro; POLIACHENKO, Ievhen; MELNYK, Galyna; CHERKES, Semen; LITVINOV, Dmytro (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. On the territory of Ukraine, where large-scale hostilities are taking place, industrial production and developed transport infrastructure are concentrated, in particular, every tenth enterprise has an increased (1st or 2nd) hazard class. Arable fields suffered no less damage from shelling and mining, which negatively affects food security in the world. The degree of ecological hazard of the territory where hostilities took place is determined primarily by the level of surface concentrations of pollutants entering the natural environment. Concentrations, as well as the range and area of dispersion of pollutants depend on the parameters of the explosion, the height of the explosion product clouds, and meteorological conditions.Methods. For war-affected areas, mechanisms for assessing the degree of mechanical damage to soils and dust from a gas-dust cloud into the environment were proposed based on methods used at mining enterprises to analyze environmental hazards.Results. The studies were carried out in the field, where ca.1000 craters of various diameters were identified. The main parameters of the explosion were estimated based on the morphological shapes of the craters: the volume of displaced (or destroyed) soil, the mass of aerosol and dust that entered the atmosphere, the width and height of the pile - the scattering of soil from the centre of the explosion. The height of the gas-dust cloud from large explosions was calculated, which is extremely important for modelling the dynamics of solid particles in the cloud and solving problems of regional pollution transportation. A sequential algorithm was developed for assessing the destruction and damage to soils and the release of aerosol and dust into the atmosphere, which is formed during ground explosions.Conclusions. An algorithm for calculating the degree of soil damage and dust ingress into the atmosphere from artillery weapons of various calibers has been proposed. Calculations of the height of the gas-dust cloud from large explosions and the scattering of earth from the crater have been obtained. The cumulative effect of soil damage and atmospheric pollution by substances from explosion products per day, month and year has been estimated. The results of comparing the damage caused to soils and emissions of harmful substances into the atmosphere as a result of the war are comparable in scale to the operation of an average quarry in Ukraine for a year. Given the scale of the battle lines environmental pollution would have catastrophic consequences.
Keywords: Russian-Ukrainian war; aerosol; dust; soil degradation